Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.2140/gt.2014.18.717
|View full text |Cite
|
Sign up to set email alerts
|

Ehrhart theory of polytopes and Seiberg–Witten invariants of plumbed 3–manifolds

Abstract: Let M be a rational homology sphere plumbed 3-manifold associated with a connected negative-definite plumbing graph. We show that its Seiberg-Witten invariants equal certain coefficients of an equivariant multivariable Ehrhart polynomial. For this, we construct the corresponding polytope from the plumbing graph together with an action of H 1 .M; Z/ and we develop Ehrhart theory for them. At an intermediate level we define the 'periodic constant' of multivariable series and establish their properties. In this w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(69 citation statements)
references
References 53 publications
1
68
0
Order By: Relevance
“…Theorem 1.14. A Brieskorn sphere Σ = Σ(p, q, r) is weakly elliptic if and only if (p, q, r) is equal to one of the following triplets: (3,4,5), (2,5,7), (2,5,9), or (2, 3, r) with gcd(6, r) = 1 and r > 5. There are no weakly elliptic Seifert homology spheres with more than three singular fibers.…”
Section: B Can and ç Karakurtmentioning
confidence: 99%
See 2 more Smart Citations
“…Theorem 1.14. A Brieskorn sphere Σ = Σ(p, q, r) is weakly elliptic if and only if (p, q, r) is equal to one of the following triplets: (3,4,5), (2,5,7), (2,5,9), or (2, 3, r) with gcd(6, r) = 1 and r > 5. There are no weakly elliptic Seifert homology spheres with more than three singular fibers.…”
Section: B Can and ç Karakurtmentioning
confidence: 99%
“…Then l 3 since only Seifert homology with less than 3 singular fibers is S 3 . Suppose l = 3, then the triple (p 1 , p 2 , p 3 ) must be greater than or equal to one of the following triples: (3,5,7), (3,4,7), (3,5,9), (2,7,9), (2,5,11), (2,5,13), (2,5,19), (2,3,19). These triples are the immediate successors of the triples appearing in the table.…”
Section: Topological Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purpose to decode the Seiberg–Witten invariants of M from f (c.f. Section 2.2), [, Reduction theorem 5.4.2] has shown that the variables of fh can be reduced to the variables of the nodes of the graph. Therefore, we restrict our discussions to the reduced zeta‐functions defined by fhfalse(tNfalse)=fhfalse(boldtfalse)|tv=1,vN.…”
Section: Introductionmentioning
confidence: 99%
“…The multivariable polynomial part Phfalse(tNfalse) associated with fhfalse(tNfalse) (defined by [, Formula (32)], see also Formula ) is mainly a combination of the one‐ and two‐variable cases studied by [, ] corresponding to the structure of the orbifold graph Γorb. The vertices of Γorb are the nodes of normalΓ and two of them are connected by an edge if the corresponding nodes in normalΓ are connected by a path which consists only vertices with valency δv=2.…”
Section: Introductionmentioning
confidence: 99%